Lexical semantic study of the Bubakan Manten Tradition in Mojodelik Village, Bojonegoro, East Java, Indonesia - Lestariningsih, Depi; Lestari, Prembayun Miji (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2024)
This research aims to analyze the lexicon contained in the bubakan manten traditional procession in Mojodelik village on AM Production's YouTube account and analyze the lexical and cultural meaning contained in the bubakan manten traditional procession in Mojodelik village on AM Production's YouTube account. This research uses a qualitative descriptive method with a lexical semantic approach. The data in this research is in the form of a lexicon contained in the bubakan manten tradition, which contains lexical and cultural meanings.  The primary data source in this research is the video of the bubakan manten tradition in Mojodelik Village, which is available on the AM Production Purwosari YouTube account, entitled Live Streaming Season 2 Langen Tayub Mustiko Laras Mojodelik Gayam, as well as interviews with the resource person who served as the leader in the implementation of bubakan manten, namely Mr. Jimin and Mr. Pandholi. Data collection techniques in this research used note-taking and interview techniques. Data analysis techniques used include sorting data for analysis, classifying lexicon forms, explaining the lexical and cultural meaning of the lexicon, and conclusion. The results of the research are a lexicon of places, equipment, food, and plants. The lexical meaning of the bubakan tradition is to open the way for marriage, while the cultural meaning contained in the bubakan tradition is to ask for safety and to be kept away from bad things.